Determination of Natural Radioactivity Levels of Some Concretes and Mineral Admixtures in Turkey - Baltas, Hasan; Kiris, Erkan; Ustabas, Ilker; Yilmaz, Esra; Sirin, Murat; Kuloglu, Emrah; Erdogan Gunes, Banu (Asian Journal of Chemistry, 2014)
Nine concrete samples with or without mineral admixtures have been analyzed for their naturally occurring radionuclide of 226Ra, 232Th and 40K using HPGe gamma spectrometry. Also, concrete raw materials such as aggregate, cement, fly ash and blast furnace slag have been measured. The radioactivity values of 226Ra, 232Th and 40K in fly ash and those of 226Ra in blast furnace slag are higher than the corresponding world mean specific activities values which are 50, 50 and 500 Bq kg-1 for 226Ra, 232Th and 40K, respectively. The concretes activity concentrations have been found to change with supplementary cementitious materials of the concrete samples. This may be attributed to containing different proportions of different mineral additives such as fly ash and blast furnace slag which were found to contain high natural radionuclide concentrations according to the rest of raw material samples. In addition, radium equivalent activities (Raeq), g-index (Ig), a-index (Ia), absorbed dose rate in air (D) and annual effective dose associated with the natural radionuclide were calculated to assess the radiation hazard of the natural radioactivity in the concrete mixture samples. The concentration of the natural radionuclides and the radium equivalent activity obtained in the present study are compared with the previous results. From these results, it can be seen that these building materials do not pose significant radiation hazards.